Efficacy of Preemergence and Sequential Applications with Corvus, Atrazine, Starane, Balance, Anthem, Capreno, Diflexx and Halex GT in Irrigated Corn - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2016)
Control of kochia and quinoa was 98 to 100% regardless of herbicide treatment at 48 days after post applications (DAPT), and 95% or more with all herbicides for Russian thistle. Palmer amaranth control was slightly less with preemergent (PRE) treatments alone compared to sequential treatments. Corvus (isoxaflutole + thiencarbazone) plus atrazine, Starane Ultra (fluroxypyr), and nonionic surfactant preemergence controlled crabgrass by 88%; whereas all other treatments provided 91% or more crabgrass control. Corn with the best herbicide treatments yielded 33 to 66 bu/a more than untreated corn.
Keywords: irrigated corn; Corvus; isoxaflutole + thiencarbazone; Starane; fluroxypyr; Diflexx; Dicamba; Halex GT; Mesotrione; Glyphosate; S-metolchlor; kochia; quinoa; Russian thistle; Palmer amaranth; crabgrass